Corporate social responsibility and firm performance: Investor preferences and corporate strategies - Mackey, Alison; Mackey, Tyson B.; Barney, Jay B. (Academy of Management Review, 2007)
We address the debate about whether firms should engage in socially responsible behavior by proposing a theoretical model in which the supply of and demand for socially responsible investment opportunities determine whether these activities will improve, reduce, or have no impact on a firm's market value. The theory shows that managers in publicly traded firms might fund socially responsible activities that do not maximize the present value of their firm's future cash flows yet still maximize the market value of the firm.